Creación de praderas diversas para servicios multi-ecosistémicos: un ejemplo de políticas de esquemas agro-ambientales impulsados por la ciencia en Reino Unido - Rivero, M. J.; Beaumont, D. A.; Griffith, B. A.; Dunn, R. M.; Orr, R. J.; Woodcock, B.; Pywell, R.; Tallowin, J. R. B. (Agro Sur, 2018)
INTRODUCTION Grassland accounts for 72% of agricultural land use in the UK and constitutes the largest area of habitat managed under the agri-environment schemes (DEFRA, 2016). Most agricultural grassland is intensively managed resulting in floristically species-poor swards supporting a restricted range of invertebrates and grassland agri-environment schemes have had a limited effect in diversifying these homogeneous habitats. Increasing grassland plant diversity can potentially provide multiple benefits including greater productivity and forage quality, increased faunal abundance and ...